Improving the smoking patterns in a general hospital psychiatric unit - Celso Iglesias García; María José Alonso Villa; Juan Carlos Bernaldo de Quirós; Elena Bocanegra Suárez; Julia Cueta Gonzalo; Rosario García del Valle; José Manuel González González; Álvaro Miranda García; Ana Belén Palacio Bande (Fundación para el Desarrollo de la Enfermería, 2009)
Objectives: The purpose of the present paper is to evaluate the effects of a smoking ban in a general hospital psychiatric unit. Methods: We study the effects of smoking ban in 40 consecutive psychiatric inpatients. The staff registered socio-demographic and tobacco-related variables. We also registered any kind of behavioral effects of smoking ban.Results: The patients were willing to stop smoking during their hospital stay (with or without nicotine replacement) with two mild behavioural incidences registered throughout the study. Conclusions: The benefits of non-smoking policy in a psychiatric unit can be significant. The introduction of smoking bans in psychiatric inpatients settings is possible and safe.